Dances in the drawing-room: musical elements in Ibsen’s dramas - Christensen, Sofija (Nordlit, 2015)
In Ibsen’s time, the piano was a powerful cultural signifier. Common ideologies, socio-cultural codes, beliefs and myths of the bourgeoisie were interwoven in the network of the piano’s metaphoric meanings. Having indeed great sensitivity for the spirit of his time, Ibsen relied on the bulk of piano’s cultural intertexts to give further depth and richness to his dramatic works. In the literature of the age the piano figured as the epicenter of social conflicts, repressed needs and emotions, as well as a distinctive marker of gender and class divisions. For Ibsen’s female protagonists music figures both as an oppressive cultural force and an expressive, creative outlet, however, the piano dances seem almost self-contradictory, having little or no notion of vitality. Although this idea of dance as the utmost life-affirming activity in the bourgeois way of life is also recognizable in Ibsen’s use of this motif, the living-room dances in Ibsen’s oeuvre are multi-layered and complex, and usually serve more than one function in the dramas. With focus on dances in Love’s Comedy, A Doll’s House, Hedda Gabler and John Gabriel Borkman the article concludes that the motif of dance in Ibsen’s dramas often serves as a specific “memento mori”, as the inbuilt vital principle of dance along with the aesthetic pleasure in the movement of the body, are coupled with their opposite: death.